Wild baby animals - Drew, Chris (Dorling Kindersley UK, 2005)
Wild Baby Animals is an engaging and educational book that introduces young readers to the lives of baby animals in the wild. Through captivating photographs and simple, informative text, the book showcases various species of wild animals, including their habitats, behaviors, and how they are cared for by their parents. Each page offers fascinating insights into the world of nature, encouraging curiosity and a love for wildlife. Perfect for young animal lovers, this book provides a fun and informative glimpse into the early stages of life for animals in the wild.